Animal Behavior : An Evolutionary Approach - Alcock, John, 1942- (Sunderland, Mass. : Sinauer Associates Inc., 2009)
This classic text continues to offer a balanced treatment of the underlying mechanisms and evolutionary bases of behaviour with a focus on the importance of evolutionary theory for the unification of the different behavioural disciplines. The new edition has been thoroughly rewritten with coverage of recent work in the field.
Includes bibliographical references and index
Keywords: Animals -- Habits and behavior; Animals -- Evolution